2000
DOI: 10.1061/(asce)0733-9399(2000)126:9(944)
|View full text |Cite
|
Sign up to set email alerts
|

Microplane Model M4 for Concrete. I: Formulation with Work-Conjugate Deviatoric Stress

Abstract: The first part of this two-part study presents a new improved microplane constitutive model for concrete, representing the fourth version in the line of microplane models developed at Northwestern University. The constitutive law is characterized as a relation between the normal, volumetric, deviatoric, and shear stresses and strains on planes of various orientations, called the microplanes. The strain components on the microplanes are the projections of the continuum strain tensor, and the continuum stresses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
176
0
4

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 252 publications
(182 citation statements)
references
References 34 publications
2
176
0
4
Order By: Relevance
“…Numerous advantages of microplane models were reviewed in and Ba zant et al (2000). One advantageous feature that has generally been overlooked in constitutive modeling but that should be emphasized is that the microplane model automatically captures the vertex effect, i.e., the fact that deformation increments that are parallel to the current loading surface in the stress space are not elastic but inelastic, as experimentally demonstrated in .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous advantages of microplane models were reviewed in and Ba zant et al (2000). One advantageous feature that has generally been overlooked in constitutive modeling but that should be emphasized is that the microplane model automatically captures the vertex effect, i.e., the fact that deformation increments that are parallel to the current loading surface in the stress space are not elastic but inelastic, as experimentally demonstrated in .…”
Section: Introductionmentioning
confidence: 99%
“…In the first version, the microplane model of concrete was only devised for tensile fracturing, but now it has been updated to the fourth version which can characterize the complicated nonlinear triaxial behavior as well as the deformation behavior under the cyclic load. The results of the numerical analysis for basic loading types with the microplane model have been compared with many actual test results and it is shown that microplane models can characterize the responses of concrete under different loading types [2] .…”
Section: Microplane Constitutive Model For Concretementioning
confidence: 99%
“…The traditional elasto-plastic-fracture constitutive models for concrete are macroscopic models. Although great success has been reached in the past, the macroscopic models now seem to have entered a period of diminishing returns, in which a great effort yields only little improvement [2] . When the concrete is under complicated stress condition, these models often can't give satisfying performance for the concrete material.…”
Section: Microplane Constitutive Model For Concretementioning
confidence: 99%
See 1 more Smart Citation
“…The model rests on two basic ideas: ͑1͒ describe these microstructural phenomena by a constitutive relation expressed not in terms of stress and strain tensors of the macroscopic continuum, but in terms of stress and strain vectors acting on planes of all possible orientations at a given point of the continuum; and ͑2͒ use a variational principle to relate the microplane vectors ͑the micro͒ to the continuum tensors ͑the macro͒. Despite increased computer time requirements, this approach has many advantages, described in detail in Bažant et al ͑2000a͒.…”
Section: Background On Microplane Approach and On Models M4 And M5mentioning
confidence: 99%